Leishmaniasis and Chagas disease: Is there hope in nanotechnology to fight neglected tropical diseases? - Scariot, Debora B.; Staneviciute, Austeja; Zhu, Jennifer; Li, Xiaomo; Scott, Evan A.; Engman, David M. (Frontiers in Cellular and Infection Microbiology, 2022)
Nanotechnology is revolutionizing many sectors of science, from food preservation to healthcare to energy applications. Since 1995, when the first nanomedicines started being commercialized, drug developers have relied on nanotechnology to improve the pharmacokinetic properties of bioactive molecules. The development of advanced nanomaterials has greatly enhanced drug discovery through improved pharmacotherapeutic effects and reduction of toxicity and side effects. Therefore, highly toxic treatments such as cancer chemotherapy, have benefited from nanotechnology. Considering the toxicity of the few therapeutic options to treat neglected tropical diseases, such as leishmaniasis and Chagas disease, nanotechnology has also been explored as a potential innovation to treat these diseases. However, despite the significant research progress over the years, the benefits of nanotechnology for both diseases are still limited to preliminary animal studies, raising the question about the clinical utility of nanomedicines in this field. From this perspective, this review aims to discuss recent nanotechnological developments, the advantages of nanoformulations over current leishmanicidal and trypanocidal drugs, limitations of nano-based drugs, and research gaps that still must be filled to make these novel drug delivery systems a reality for leishmaniasis and Chagas disease treatment.